L-rhamnose-binding lectins (RBLs) in Nile tilapia, Oreochromis niloticus: Characterization and expression profiling in mucosal tissues. Issue 72 (January 2018) - Zhang, Dongdong; Beck, Benjamin H.; Mohammed, Haitham; Zhao, Honggang; Thongda, Wilawan; Ye, Zhi; Zeng, Qifan; Shoemaker, Craig A.; Fuller, S. Adam; Peatman, Eric
Abstract: Rhamnose-binding lectins (RBLs) are crucial elements associated with innate immune responses to infections and have been characterized from a variety of teleost fishes. Given the importance of RBL in teleost fishes, we sought to study the diversity and expression profiles of RBLs in an important cultured fish, Nile tilapia ( Oreochromis niloticus ) following experimental infection with Streptococcus agalactiae, a major cause of streptococcosis in farmed tilapia. In this study, four predicted RBL genes were identified from Nile tilapia and were designated as OnRBL3a, OnRBL3b, OnRBL3c, and OnRBL3d. These OnRBLs were composed of two tandem-repeated type five carbohydrate recognition domains (CRDs), classified as type IIIc, and all clustered together phylogenetically. OnRBL-CRDs shared conserved topology of eight cysteine residues, characteristic peptide motifs of -YGR- and -DPC- (or -FGR- and -DTC-), and similar exon/intron organization. OnRBLs had the highest expression in immune-related tissues, gills, intestine or liver. However, the changes of OnRBL expression in the gills and intestine at 2 h, 4 h and 24 h post S. agalactiae challenge were modest, suggesting that tilapia may not mediate the entry or confront the infection of S. agalactiae through induction of RBL genes. The observed expression pattern may be related to the RBL type and CRD composition, S. agalactiae pathogenesis, the accessibility of ligands on the bacterial surface, and/or the species of fish. OnRBLs characterized in this study were the first RBL members identified in Nile tilapia and their characterization will expand our knowledge of RBLs in immunity. Highlights: Four predicted RBL genes were identified from Nile tilapia. OnRBLs are type IIIc with two type five carbohydrate recognition domains. Changes of OnRBL expression post Streptococcus agalactiae infection were modest.